Mechano-responsive microcapsules with uniform thin shells. Issue 6 (23rd November 2018) - Vian, A.; Amstad, E.
Abstract : We introduce micrometer-sized capsules whose shells occupy as little 2% of their volumes. We demonstrate that these capsules are mechanically stable and have a low permeability even towards small encapsulants during storage. Abstract : Capsules often prolong the shelf-life of active ingredients, such as many types of drugs, food additives, or cosmetic substances, because they delay oxidation of these substances or prevent their reactions with molecules contained in the surrounding. If capsules are appropriately designed, they can offer an additional benefit: they allow close control over the timing and location of the release of active ingredients. To take advantage of these features, capsules must possess shells whose thickness and composition are well-defined. However, the shell thickness of capsules often varies considerably even within a single capsule, thereby hampering good control over the release kinetics of encapsulants. These variations can be reduced, and hence the degree of control over the release kinetics increased, if shells are made thin. Unfortunately, the controlled fabrication of mechanically stable microcapsules with well-defined sub-μm thick shells is difficult. Here, we introduce a method to fabricate capsules with uniform semi-permeable shells with a thickness as low as 400 nm. This is achieved using water–oil–water double emulsions with 800 nm thick shells as templates to fabricate capsules with uniform 400 nm thin shells. These shells occupy less than 2% of the capsule volume, thereby minimizing their footprint. Despite their thin shells, these capsules are mechanically robust: they withstand pressures up to 1.3 MPa without deformation and remain intact if exposed to pressures up to 2.75 MPa. Moreover, while they are permeable towards water, they retain low molecular weight encapsulants even if dried and re-dispersed. The thin shells of the capsules open up new possibilities of their use to functionalize materials with at least one dimension that is small, such as coatings, where thick shells introduce defects, or as building blocks of new types of functional materials.